2020
DOI: 10.18400/tekderg.470633
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors that Contribute to Severity of Construction Injuries using Logistic Regression Model

Abstract: Majority of research in occupational safety and health area lean towards describing accidents with the aid of surveys and descriptive statistics, instead of using inferential statistical techniques. Therefore, an extensive archival study was performed in cooperation with Social Security Institute of Turkey, which included examination and reorganization of more than 2000 accident report forms to create a categorically identified data set, incorporating "Injury Severity Score" concept, followed by various statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
1
5
0
1
Order By: Relevance
“…In the construction sector, the most common type of accident is falls from height. Akbo ga and Baradan (2020) found that "falls" and "struck by falling object" were the two most noticeable data with 36.4% and 30.0% frequencies, respectively [25]. These findings show similarities with past studies.…”
Section: Occupational Safety and Potential Hazards In Historic Buildingssupporting
confidence: 76%
See 2 more Smart Citations
“…In the construction sector, the most common type of accident is falls from height. Akbo ga and Baradan (2020) found that "falls" and "struck by falling object" were the two most noticeable data with 36.4% and 30.0% frequencies, respectively [25]. These findings show similarities with past studies.…”
Section: Occupational Safety and Potential Hazards In Historic Buildingssupporting
confidence: 76%
“…should be taken against situations such as some parts of the restored building breaking off, breaking, and falling over. That the area around the repaired area should be covered with a railing and a net should be drawn between the railing also suggested that the areas where work is carried out should be covered with railings and a net or wire mesh should be drawn between the railings [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kış aylarında meydana gelen iş kazalarında kazazedenin genel iş deneyimi arttıkça kaza şiddetinin azaldığı bulgusuna ulaşılmıştır. Bu bulgunun literatürdeki bazı araştırmacılar (Akboğa ve Baradan, 2019;Dumrak vd., 2013) tarafından mevsimsel ayrım yapılmaksızın iş kaza şiddeti ve çalışan deneyimi arasındaki ilişkinin araştırıldığı çalışmalar ile uyum içinde olduğu görülmüştür.…”
Section: Analiz Varsayımlarıunclassified
“…The construction industry is one of the most hazardous industries in the world because of its diverse and complex nature [1][2][3][4][5][6][7]. Moreover, the construction industry ranks higher in fatal occupational injuries than any other sector due to the nature of work [8][9][10][11][12]. So, it mandates that the activities of construction industry have to be studied and further analyzed for reducing accident rates.…”
Section: Introductionmentioning
confidence: 99%